A broad-spectral-response perovskite photodetector with a high on/off ratio and high detectivity. (16th August 2018) - Yi, Xiaohui; Wang, Yisen; Chen, Ningli; Huang, Zhiwei; Ren, Zhenwei; Li, Hui; Lin, Tao; Li, Cheng; Wang, Jizheng
Abstract : We designed and fabricated a CH3 NH3 PbI3 /TiO2 /Si hybrid photodetector, which shows a high on/off ratio, high detectivity and broad photoresponse. Abstract : Given their high photoconversion efficiency, organometal halide perovskites have attracted much interest in ultraviolet-visible-near infrared photodetectors (PDs). However, recombination of carriers in perovskites, which leads to low photocurrent, has always been an adverse factor for device performance. Here, we demonstrate a way to overcome this problem by incorporating technologically-mature Si. Meanwhile, the dark current of the device can be maintained at a low level after inserting a TiO2 layer between the CH3 NH3 PbI3 film and the Si substrate. The fabricated CH3 NH3 PbI3 /TiO2 /Si tri-component PD displays a high on/off ratio of 6 × 10 3 and a high detectivity of 4.85 × 10 13 Jones. In addition, the PD shows broad photoresponse with a long cut-off wavelength of 1100 nm. The design here provides an intriguing way for improving perovskite-based PDs.